Winds of fate Book One of The Mage Winds - Lackey, Mercedes (DAW Books New York, 1994)
High magic has been lost to Valdemar centuries ago when the last Herald-Mage gave his life to save the kingdom from destruction by dark sorceries. Yet now the realm is at risk again. And Elspeth, Herald and heir to the throne, must take up the challenge, abandoning her home to find a mentor who can awaken her untrained mage abilities. But other, too are being caught up in a war against sorcerous evil. The Tayledras scout Darkwind is the first to stumble across the menace creeping forth from teh "Uncleansed Lands". And as sorcery begins to take its toll, Darkwind may be forced to call upon powers he has sworn never to use again if he and his people are to survivve an enemy able to wreak greater devastation with spells of destruction than with swords. . .
94612
Keywords: Science fiction; Fantasy; Magic; Heiresses